Peer Reviewer : TEKNIK PENERJEMAHAN SANDING KATA : SUATU TINJAUAN TEORETIS - Zainuddin . (BAHAS, 2014)
ABSTRACT The aims of the present study are to describe the tehnique of translating English collocations and Indonesian collocation. The tehnique of translating the subject matters by comparing the patterns of English collocations and the Indonesian collocations in terms of lexical collocation and grammatical collocation as source of translation studies. The source of the translation studies based on the writer’s teaching experiences from Postgraduate Studies teaching the subject matters of collocations at the English Applied Linguistics Study Program Postgraduate School, State University of Medan academic year of 2013/201. Key Words: tehnique, collocation,patterns